Nietzsche on Kant and teleology in 1868: '"life" is something entirely dark … '. Issue 1 (2nd January 2019) - Gardner, Sebastian
ABSTRACT: We know from Nietzsche's posthumously published notebooks and correspondence of his plan in 1868 to compose a doctoral dissertation in philosophy on the subject of teleology in nature and the concept of the organic, with reference to Kant. The bulk of my discussion represents an attempt to extrapolate from Nietzsche's letters and preparatory notes the view he arrived at. Since the notes do not defend explicitly any single definitive thesis, their interpretation is unavoidably conjectural. I argue that, if Nietzsche's remarks are considered with close reference to the philosophers who at that point dominated his horizons, namely Kant, Schopenhauer, and Lange, with Goethe also playing a key role, a plausible account can be given of the broad conclusions Nietzsche reached as a result of his early engagement with the problem of teleology. This outlook maintains the necessity and distinctiveness of philosophical reflection, but takes a skeptical view of its basis. In 1868 Nietzsche had no clear idea of how to proceed from this point, but in the end I propose, as others have done, that Nietzsche's reflections on Kant and teleology helped to lay the ground for The Birth of Tragedy . In conclusion, I hypothesize that Nietzsche's later philosophy involves no change of metaphilosophical standpoint.